Legal Education for Non-Lawyers as ‘Legal First Aid': A Participatory Inquiry into Law for Social Work Students - Stephen Rigby; Daniel Toohey; Lisa Toohey; Donna McNamara (Legal Education Review)
The article documents the experience of the authors in creating and re-calibrating a compulsory legal module within a Bachelor of Social Work degree as a course in 'legal first aid'. The article explores the pedagogical approach the authors developed, which is based on continually explaining to students the reason for studying law in a way that is tailored to skills they can use in their practical placements and profession. For social work students, the 'legal first aid' approach enabled them to develop confidence and skills in triaging the seriousness of particular situations, understanding what they can do in the short term, and knowing how and when to usefully engage with legal professionals.